Logo Redesign as an Effort to Strengthen the Identity of Sanggar X Talent Dance Official Surabaya - Deby Rahmawati; Sri Wulandari; Aditya Rahman Yani (fakultas Desain Komunikasi Visual, 2025)
The widespread access to popular culture through digital media has an impact on increasing public taste for modern art. Changes in trends that dominate various social platforms are often considered more relevant or cool compared to traditional art which may be considered old-fashioned or outdated. Therefore, interaction with traditional art is needed to educate and inspire teenagers' interest in local cultural diversity. In overcoming this challenge, a studio is needed as a place for activities that support the development of art and culture. As with dance studios in Surabaya that create dances to be performed at festivals and competitions between regions to show how diverse and dynamic dance art is. Thus, the purpose of the logo redesign on the Sanggar XTD Official Surabaya is to build and develop the image of the studio which is more consistent and professional. This effort is made by adjusting the logo design to the tastes of today's teenagers so that they are willing to be involved in dance. The research method used is a mixed method (qualitative and quantitative) based on a descriptive analysis approach. Primary data collection techniques are carried out through interviews, observations and questionnaires, while secondary data collection is through literature studies. Formulating design concepts, such as keywords , verbal concepts, visual concepts and media concepts are some important aspects that also need to be considered in making a logo. Thus, it is hoped that the logo redesign strategy will play an effective role in creating a fresher visual identity and be able to present the studio by adopting a modern design without abandoning traditional values.